Description of Acrolobus longigubernaculum sp. n. (Nematoda, Rhabditida, Cephalobidae) from Iran, the second species of the genus - Amirzadi, Negin; Shokoohi, Ebrahim; Eskandari, Ali; Abolafia, Joaquín (Zootaxa, 2012)
A new species of the genus Acrolobus was recovered during a survey of soil nematodes. Acrolobus longigubernaculumsp. n., collected from the rhizosphere of weeds in northeastern Iran, is described and illustrated. It is characterized by abody length of 0.72–0.98 mm in females and 0.73–0.84 mm in males, annulated cuticle, lateral fields with three longitu-dinal incisures, lip region slightly offset from the neck and 8–11μm wide, lips leaf-like, stoma 12–16 µm long, pharyngealcorpus 2.7–3.2 times isthmus length, vulva located slightly posterior to middle of body (V = 61–65), spermatheca 26–46µm long, postuterine sac 27–49 µm long or 0.9–1.3 times the corresponding body diameter, female tail conical with a fine,short mucro (47–58 µm, c = 13.9–18.5, c’ = 2.4–3.2), male tail conical bearing a fine mucro (47–50 µm, c = 14.8–17.5;c’ = 2–2.3), spicules 26–30μm long and ventrally curved, and gubernaculum 12–16 µm long (50% of spicule length). The new taxon is the second species of the genus Acrolobus and is compared to the type species, A. emarginatus.